Renin–Angiotensin Inhibition and Outcomes in Nursing Home Residents With Heart Failure. (May 2020) - Arundel, Cherinne; Sheriff, Helen M.; Lam, Phillip H.; Mohammed, Selma F.; Jones, Linda G.; Jurgens, Corrine Y.; Morgan, Charity J.; Faselis, Charles; Allman, Richard M.; Fonarow, Gregg C.; Ahmed, Ali
Abstract : Background: Angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (ACEIs-ARBs) improve outcomes in heart failure (HF). Less is known about this association in nursing home (NH) residents. Methods: Of the 8024 hospitalized HF patients, 542 were NH residents, of whom 250 received ACEIs-ARBs. We assembled a propensity score–matched cohort of 157 pairs of NH residents receiving and not receiving ACEIs-ARBs balanced on 29 baseline characteristics (mean age, 83 years, 74% women, 17% African American), in which we estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for outcomes associated with ACEI-ARB use. We then checked for interaction in a matched cohort of 5130 patients (378 were NH residents) assembled from the 8024 patients. Results: Among 314 matched NH residents, HRs (95% CIs) for 30-day all-cause readmission, HF readmission, and all-cause mortality were 0.78 (0.47–1.28), 0.68 (0.29–1.60), and 1.26 (0.70–2.27), respectively. Respective HRs (95% CIs) at 1 year were 0.76 (0.56–1.02), 0.68 (0.42–1.09), and 1.04 (0.78–1.38). Among 5130 matched patients, ACEI-ARB use was associated with a significantly lower risk of all outcomes at both times, with no significant interactions, except for 1-year mortality, which was only significant in the non-NH subgroup ( P for interaction, 0.026). Conclusions: We found no evidence that the use of ACEIs or ARBs is associated with improved outcomes in patients with HF in the NH setting. However, we also found no evidence that this association is different in NH residents with HF versus non-NH patients with HF. Future larger studies are needed to demonstrate effectiveness of these drugs in the NH setting.